Modulation of Cellular NAD+ Attenuates Cancer-Associated Hypercoagulability and Thrombosis via the Inhibition of Tissue Factor and Formation of Neutrophil Extracellular Traps - Wa Cao (MDPI AG, 2021)
Cancer-associated thrombosis is the second-leading cause of mortality in patients with cancer and presents a poor prognosis, with a lack of effective treatment strategies. NAD(P)H quinone oxidoreductase 1 (NQO1) increases the cellular nicotinamide adenine dinucleotide (NAD+) levels by accelerating the oxidation of NADH to NAD+, thus playing important roles in cellular homeostasis, energy metabolism, and inflammatory responses. Using a murine orthotopic 4T1 breast cancer model, in which multiple thrombi are generated in the lungs at the late stage of cancer development, we investigated the effects of regulating the cellular NAD+ levels on cancer-associated thrombosis. In this study, we show that dunnione (a strong substrate of NQO1) attenuates the prothrombotic state and lung thrombosis in tumor-bearing mice by inhibiting the expression of tissue factor and formation of neutrophil extracellular traps (NETs). Dunnione increases the cellular NAD+ levels in lung tissues of tumor-bearing mice to restore the declining sirtuin 1 (SIRT1) activity, thus deacetylating nuclear factor-kappa B (NF-κB) and preventing the overexpression of tissue factor in bronchial epithelial and vascular endothelial cells. In addition, we demonstrated that dunnione abolishes the ability of neutrophils to generate NETs by suppressing histone acetylation and NADPH oxidase (NOX) activity. Overall, our results reveal that the regulation of cellular NAD+ levels by pharmacological agents may inhibit pulmonary embolism in tumor-bearing mice, which may potentially be used as a viable therapeutic approach for the treatment of cancer-associated thrombosis.